THE INFLUENCE OF IMPLEMENTING PORTFOLIO ASSESSMENTS IN SCIENCE LEARNING ON STUDENT LEARNING OUTCOMES: A SYSTEMATIC REVIEW - Ulfa, Jufiani; Aldilla, Endang; Mufit, Fatni; Festiyed, Festiyed (Program Studi Pendidikan Fisika FKIP Universitas Jambi, 2023)
This literature review aims to investigate how the portfolio assessment used in research influences the learning outcomes of students based on the objectives of the analysis, research design used, level of education, learning topic, and form of an assessment tool. The most significant benefit of portfolio assessment was obtained in applied research/influence/effectiveness, namely 61.54%. Science learning with a research design had the highest frequency in a quasi-experimental design of 42.31%. The level of education was another factor that affected the portfolio assessment of science learning. Portfolio assessment in science learning was more prevalent at the upper secondary education level, with a percentage of 57.69%. The application of portfolio assessment in science learning (integrated science, physics, and biology) revealed that physics subjects attracted more research interest, namely 50%. Based on the research results and discussion presented in this article, it can be concluded that the portfolio assessment of science learning can be used at various levels of education. The novelty of this research is that it synthesizes the existing literature on the impact of implementing portfolio assessment in science learning on learning outcomes. Portfolio assessment in science learning implies that it can arouse students’ interest in the subject, motivate them to engage in active learning, improve students’ mastery of topics, and inform parents of their child’s educational progress. Future research may explore other aspects of portfolio assessment, such as its validity, reliability, and feedback mechanisms.